An energy conservation method for locating wireless sensor network nodes in smart grid - Chong WANG; Zeng ZENG (Dianxin kexue)
Wireless sensor network has been increasingly applied for detecting，monitoring and locating targets in smart grid.In a wireless sensor network，energy is deemed as a critical resource and life of the system can be prolonged by energy saving strategy.A node detection and localization method based on energy-aware was presented.The method could be used for the clustering-based wireless sensor networks.It employed a posterior algorithm using a two-step communication protocol between the clustering head sensor and sensors inside.Only a small amount of node information was needed for the clustering head to run the localization program to determine the subset of sensors for further localization.In this way，consumption of energy and demand for communication bandwidth could be reduced，and the system life could be prolonged as well.Experiment results show that this locating method is able to save up to 32% of energy.